Dysbiosis of skin microbiota with increased fungal diversity is associated with severity of disease in atopic dermatitis. (7th July 2022) - Schmid, B.; Künstner, A.; Fähnrich, A.; Bersuch, E.; Schmid‐Grendelmeier, P.; Busch, H.; Glatz, M.; Bosshard, P.P.
Abstract: Background: Atopic dermatitis (AD) is a multifactorial inflammatory skin disease and an altered skin microbiota with an increase of Staphylococcus aureus has been reported. However, the role of fungi remains poorly investigated. Objectives: We aimed to improve the understanding of the fungal skin microbiota, the mycobiota, in AD in relation to the bacterial colonization. Methods: Skin swabs of 16 AD patients and 16 healthy controls (HC) from four different skin sites, that is antecubital crease, dorsal neck, glabella and vertex from multiple time points were analysed by DNA sequencing of the internal transcribed spacer region 1 (ITS1) and 16S rRNA gene for fungi and bacteria, respectively. Results: Malassezia spp. were the predominant fungi in all subjects but with a decreased dominance in severe AD patients in favour of non‐ Malassezia fungi, for example Candida spp. For bacteria, a decrease of Cutibacterium spp. in AD patients in favour of Staphylococcus spp., particularly S. aureus, was observed. Further, both bacterial and fungal community compositions of severe AD patients significantly differed from mild‐to‐moderate AD patients and HC with the latter two having overall similar microbiota showing some distinctions in bacterial communities. Conclusions: We conclude that severe AD is associated with a pronounced dysbiosis of the microbiota with increased fungal diversity. Potentially infectious agents, for example Staphylococcus and Candida, were increased in severe AD.